(untitled) (The Review of Diabetic Studies, 2025)
Background: Diabetes mellitus (DM) has been associated with impaired immune function, delayed tissue healing, and increased susceptibility to infections, including apical periodontitis (AP). Endodontic management in diabetic patients presents unique clinical challenges due to these systemic alterations. Objective: This systematic review aimed to evaluate the effectiveness of root canal disinfection protocols and the prevalence of AP in diabetic versus non-diabetic populations, integrating clinical, radiographic, and microbiological outcomes. Methods: A comprehensive literature search was conducted in PubMed, Scopus, Web of Science, Embase, and Google Scholar for studies published between January 2010 and December 2025. Eligible studies included cross-sectional analyses, prospective cohorts, and randomized clinical trials comparing diabetic and non-diabetic patients undergoing root canal therapy. Data extraction focused on AP prevalence, disinfection efficacy, and post-treatment healing outcomes. Risk of bias was assessed using the Newcastle–Ottawa Scale and Cochrane RoB 2 tool. Results: Eleven studies met inclusion criteria. Diabetic patients consistently exhibited higher AP prevalence than non-diabetic controls (range: 13.5–74%). Type 1 and type 2 diabetes were associated with increased lesion persistence and delayed periapical healing. Controlled diabetes allowed for comparable healing outcomes following endodontic treatment. Enhanced irrigation techniques, including ultrasonic activation and photon-induced photoacoustic streaming, demonstrated superior microbial reduction compared to conventional syringe irrigation. Lower concentrations of sodium hypochlorite (1%) were effective and safe for periapical tissues. Conclusion: Diabetes mellitus predisposes patients to higher AP prevalence and may compromise root canal healing, particularly in poorly controlled cases. Optimized disinfection protocols and meticulous clinical techniques are essential for successful outcomes. Integration of systemic health assessment with endodontic management is recommended to enhance both oral and systemic health in diabetic populations.